2009
DOI: 10.1182/blood-2008-08-172155
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 contributes to CD4-mediated graft-versus-host disease

Abstract: IntroductionThus far, 3 subsets of proinflammatory helper T cells have been described: Th1, Th2, and Th17 cells. 1 Naive T cells exposed to interleukin-12 1 (IL-12) differentiate into Th1 cells, resulting in expression of Tbet and STAT4, and secretion of interferon (IFN)-␥. 2 Th1 cells are essential for the clearance of intracellular bacteria and negatively regulate the development of Th2 and Th17 cells. 2 IL-4 activates a Th2 program, characterized by expression of STAT6 and GATA3 and secretion of IL-4, IL-5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(223 citation statements)
references
References 46 publications
11
208
2
2
Order By: Relevance
“…The role of IL-17-producing Thelper cells is increasingly being recognized in GvHD. [63][64][65][66][67] Tournadre et al 68 recently showed by analyzing muscle biopsies of patients with inflammatory myopathies that IVIG could mediate their immunomodulation by acting on the Th17 pathway. One could speculate that IVIG exert their modulatory effect on GvHD by impairing the Th17 pathway, although more analysis on other Th17-family cytokines and on the nature of IL-17 secreting cells in our model will be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL-17-producing Thelper cells is increasingly being recognized in GvHD. [63][64][65][66][67] Tournadre et al 68 recently showed by analyzing muscle biopsies of patients with inflammatory myopathies that IVIG could mediate their immunomodulation by acting on the Th17 pathway. One could speculate that IVIG exert their modulatory effect on GvHD by impairing the Th17 pathway, although more analysis on other Th17-family cytokines and on the nature of IL-17 secreting cells in our model will be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…116 In contrast, a second study using a similar model showed that IL-17 contributes to CD4-mediated GVHD without affecting the OS rates. 117 In addition, the differentiation of Th17 cells in vitro appears to cause lethal acute GVHD with severe cutaneous and pulmonary damage. 118 These conflicting results may be due to variations among the model systems, and further analyses are required to define the role of Th17 cells in GVHD.…”
Section: Exogenous Administration Of Ifn-g or T Cells From Ifn-g-defimentioning
confidence: 99%
“…12 This could be relevant as Th17 responses were shown to be involved in GvHD. 13 The application of Syk inhibitors has been successfully tested in murine models of glomerulonephritis, 14 lupus 15,16 and rheumatoid arthritis. 17 Although initial studies were performed with broader protein tyrosine kinase inhibitors such as Curcumin or Piceatannol, recently more specific Syk kinase inhibitors, such as Syk Inhibitor I to IV or R406, of which the orally bioavailable prodrug is R788 (Fostamatinib) have been developed and safely tested in humans.…”
Section: Introductionmentioning
confidence: 99%